Multiple Duties for Spindle Assembly Checkpoint Kinases in Meiosis - Marston, Adele L.; Wassmann, Katja (Frontiers in Cell and Developmental Biology, 2017)
Cell division in mitosis and meiosis is governed by evolutionary highly conserved protein kinases and phosphatases, controlling the timely execution of key events such as nuclear envelope breakdown, spindle assembly, chromosome attachment to the spindle and chromosome segregation, and cell cycle exit. In mitosis, the spindle assembly checkpoint (SAC) controls the proper attachment to and alignment of chromosomes on the spindle. The SAC detects errors and induces a cell cycle arrest in metaphase, preventing chromatid separation. Once all chromosomes are properly attached, the SAC-dependent arrest is relieved and chromatids separate evenly into daughter cells. The signaling cascade leading to checkpoint arrest depends on several protein kinases that are conserved from yeast to man. In meiosis, haploid cells containing new genetic combinations are generated from a diploid cell through two specialized cell divisions. Though apparently less robust, SAC control also exists in meiosis. Recently, it has emerged that SAC kinases have additional roles in executing accurate chromosome segregation during the meiotic divisions. Here we summarise the main differences between mitotic and meiotic cell divisions, and explain why meiotic divisions pose special challenges for correct chromosome segregation. The less-known meiotic roles of the SAC kinases are described, with a focus on two model systems: yeast and mouse oocytes. The meiotic roles of the canonical checkpoint kinases Bub1, Mps1, the pseudokinase BubR1 (Mad3), and Aurora B and C (Ipl1) will be discussed. Insights into the molecular signaling pathways that bring about the special chromosome segregation pattern during meiosis will help us understand why human oocytes are so frequently aneuploid.